Dari Kelas Konvensional ke Pembelajaran Berbasis Digital - Jusman Jusman; Chairan Zibar L. Parisu (Journal of Humanities, Social Sciences, and Education, 2025)
The transition from conventional classrooms to digital-based learning has become an inevitable global phenomenon, especially in response to technological advancements and the evolving needs of 21st-century learners. This literature review aims to explore the paradigm shift in education from traditional face-to-face models to digital systems, highlighting the driving and inhibiting factors of this process. The analysis draws from recent sources discussing innovations in digital learning, infrastructure readiness, changes in the educator’s role, and new skills required by students. The findings indicate that digital-based learning offers flexibility, accessibility, and personalization, while also presenting challenges such as the digital divide, limited social interaction, and the need for digital competence training for teachers and students. The implications suggest the necessity for a well-planned transition strategy, adequate resource provision, and adaptive curriculum development that integrates technology. With the right approach, digital learning holds the potential to enhance education quality and expand access across diverse communities. This study is expected to serve as a reference for education practitioners, policymakers, and researchers in understanding the dynamics of this transformation and in designing more innovative and inclusive learning models.